Electrocautery vs. Stapler in Comparing Safety for Segmentectomy of Lung Cancer: A Meta-Analysis - Lu, Tianjian; Zhang, Ruoxi; Jiang, Kexin; Wang, Zihuai; Hao, Xiaohu; Chen, Nan; Liu, Lunxu (Frontiers in Surgery, 2021)
Background: Electrocautery and staplers are regarded as the two most common surgical instruments for dissecting intersegmental plane in segmentectomy. We performed a meta-analysis to compare electrocautery and staplers in terms of their safety and effects. Methods: A systematic search strategy was made using PUBMED, the retrieval time was up to 1st April 2020. . Odds ratio and mean differences with 95% confidential interval were applied to determine the effectiveness of dichotomous or continuous variables respectively. Results: 6 studies including 385 patients were included. The electrocautery had a higher incidence rate of postoperative complication[OR= 1.92, 95%CI (1.12, 3.28), P=0.02)] and air leak[OR: 3.91, 95%CI (1.64, 9.35), P=0.002)]. No significant difference were found in comparison of surgery time, blood loss, duration tube days or hospitality days. Conclusion: Our study indicated that patients under segmentectomy was associated with a better safety by using stapler than electrocautery in the reduction of postoperative complications.